KEBIJAKAN HUTANG, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PERTAMBANGAN - Diana, Fina; Mannaga, Idham; Setiadi, Farhan Wahyu (Patria Artha Journal of Accounting dan Financial Reporting, 2023)
The effect of debt policy, profitability and dividend policy to firm value of mining on the IDC in 2016-2021. The analytical method used is descriptive statistics, gives a brief description of the results of the research test, and uses the classical assumption test, hypothesis testing using multiple linear regression analysis and the coefficient of determination. The results of this study indicate that partially there is no influence and no significant debt policy on the value of mining companies on the IDX in 2016-2021. Partially there is no influence and no significant profitability on the value of mining companies on the IDX in 2016- 2021. Furthermore, there is a partial and significant effect of dividend policy on the value of mining companies on the IDX in 2016-2021. Simultaneously the independent variables of debt policy, profitability, and dividend policy have a significant and significant effect on the value of mining companies on the IDX in 2016-2021.